Analysis of a Hybrid Rack-type Dryer Made of Polycarbonate for Drying Pisang Sale - Lubis, Muhammad Iqbal Abdi; Nasution, Afrilia Maharani; Putri, Irriwad; Hasibuan, Halimatus Syahdia (Universitas Brawijaya, 2025)
The drying of bananas as raw material for banana chips still often uses traditional methods that depend on weather and contaminants, which often pose challenges in maintaining quality and production efficiency, especially in Pasaman Barat District. The objective of this study is to analyze a hybrid rack-type dryer made of polycarbonate as an alternative solution for banana chip processing. This study employed an experimental method with a randomized block design (RBD) with three treatment groups for drying energy sources, including: sunlight (P1), incandescent lamp (P2), and sunlight + incandescent lamp (P3). The data were analyzed using the ANOVA test (p<0.05). The parameters observed in this study were: drying time, moisture content, temperature, working capacity, drying rate, heat loss, energy required to evaporate water from the material, and drying energy efficiency. The use of incandescent lamps in banana chip drying was proven to be the most efficient and effective, with an average drying time of 9 hours (2 hours and 3 hours shorter than P3 and P1, respectively), a working capacity of 0.18 kg/hour, moisture content <40% (in accordance with SNI 01-4319-1996 standards), drying rate of 0.07 kg/hour, heat loss of 28.39 W, and energy required to evaporate the material's water content of 1,391.55 kJ. Meanwhile, the drying energy efficiency of P3 is 1.58 times and 1.64 times higher than P2 and P1, respectively, at 59.80%. Thus, this device is deemed suitable for use as a new, more effective and efficient method for drying banana chips.